Chemical Castration Sanctions in an Ethical Perspective - Yovita Arie Mangesti; Slamet Suhartono (Jambura Law Review, 2022)
Chemical castration sanctions are additional sanctions imposed on perpetrators of sexual violence against children. This sanction was imposed as an implementation of the child protection law. This additional sanction is threatened with the consideration that every act of sexual violence leaves a psychological trauma for the child that affects the child's growth and development in his life. However, this is a paradox with the aim of restorative justice theory as a new vision in criminal law enforcement. With a statutory, conceptual, and scholastic approach to the Implementing Regulations of Chemical Castration with ethical perspective parameters, the imposition of additional sanctions is unethical and in harmony with restorative justice that prioritizes human values for perpetrators, victims, and executor of chemical castration. The imposition of sanctions should pay attention to the principle of respect for human values as a whole person (respect for person) and the principle of access to justice (justice for all).